A simple and rapid extraction for gas chromatographic determination of thiabendazole and imazalil residues in lemons - Navickiene, Sandro [UNESP]; Ribeiro, Maria Lúcia [UNESP] (FapUNIFESP (SciELO), 2002)
A rapid and efficient method is described for the determination of thiabendazole and imazalil residues in lemons (peel and pulp). The procedure is based on the extraction with an hexane:ethyl acetate mixture (1:1, v/v) and gas chromatographic analysis using thermionic specific detection (TSD). The possibility of matrix effect was also studied. Mean recoveries from 8 replicates of fortified samples ranged from 79% to 109%, with relative standard deviation values between 2.4% to 12.8%. The detection and quantification limits of the method were 0.2 mg kg-1 and 0.5 mg kg-1, respectively.
Keywords: Gas chromatography; Imazalil; Lemon; Pesticide residues; Thiabendazole; enilconazole; tiabendazole; chemical analysis; concentration (parameters); extraction; gas chromatography; lemon